The Implementation of Clinical Supervision as a Strategy for Enhancing Teachers’ Professional Competence in Senior High Schools: A Case Study - Nur Irma Fitriani; Anisa Kumala Ningrum; Marselus Kelanangame; Soedjono Soedjono (Lembaga Teewan Journal Solutions, 2026)
Teachers' professional competence is essential for improving learning quality; however, school supervision is often focused on administrative compliance rather than continuous instructional improvement. This study aimed to analyze the implementation of clinical supervision through the pre-observation, classroom observation, and post-observation stages in enhancing teachers' professional competence at SMA Negeri 1 Rembang. A qualitative approach with a case study design was employed. The participants consisted of the principal as the supervisor and teachers who participated in clinical supervision, selected using purposive sampling. Data were collected through observations, in-depth interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the pre-observation stage established collaborative agreements on the supervision focus, the classroom observation stage generated objective evidence of instructional practices as the basis for feedback, and the post-observation stage encouraged teachers to reflect on and continuously improve their teaching practices. The study concludes that the effectiveness of clinical supervision depends on the integration of its three stages through a collaborative and reflective process. The novelty of this study lies in identifying the specific contribution of each stage of clinical supervision in strengthening teachers' professional competence as a sustainable professional development model.